Dampak Media Sosial untuk Partisipasi Politik dan Keterlibatan Sipil di Delta State - Oghiagbepha, Oghenekevwe; Okwuokei, Vivian Chekube; Ivwighren, Hannah Emuobosa (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2025)
This study investigates the influence of social media on political involvement and public involvement activities throughout Delta State alongside its capacity to expedite immediate information distribution public discussions and community organization. According to the Uses and Gratifications Theory, individuals select their social media engagement through personal objectives and political beliefs. Ethiope East and Ethiope West are the main focus while Isiokolo and Oghara town were specifically selected as the population for the study. A sample size of 400 participants revealed that participants follow political news on social media platforms. A structured questionnaire was distributed electronically and in hardcopies to collect data on social media usage patterns, political participation, and civic engagement levels. The data analysis was done using descriptive and inferential statistics as Spearman Rank was used to test the hypothesis. The analysis showed that political accessibility depends on cultural collectives together with political capacity, social constraints, education, and economic background. It is recommended therefore that governments, academic institutions, and civil society organisations should create programs to teach citizens how to differentiate between reliable political information and false information, guaranteeing responsible and informed civic engagement by improving their critical thinking and digital.